Increased Vulnerabilities: Considering the Effects of Xeno-Racist Ordering for Romanian Migrant Sex Workers in the United Kingdom - Sam Hanks (International Journal for Crime, Justice and Social Democracy, 2021)
AbstractThis article draws on data from interviews with sex workers in Welsh massage parlours and individuals involved in the provision of support to migrant sex workers in Wales and England. Drawing on concepts of xeno-racism and ‘everyday ordering’, it illustrates the ways in which violence against sex workers is enabled by policies and state institutions in a way that is increasingly mediated and compounded by race and immigration status. It argues that an awareness of regular and hostile policing practices, coupled with fears of deportation amongst a sample of primarily Romanian migrant sex workers are exposing them to increased risks of harm and exploitation.